Reporting and conducting patient journey mapping research in healthcare: A scoping review. (3rd November 2022) - Davies, Ellen L.; Bulto, Lemma N.; Walsh, Alison; Pollock, Danielle; Langton, Vikki M.; Laing, Robert E.; Graham, Amy; Arnold‐Chamney, Melissa; Kelly, Janet
Abstract: Aim: To identify how patient journey mapping is being undertaken and reported. Design: A scoping review of the literature was undertaken using JBI guidance. Data Sources: Databases were searched in July 2021 (16th–21st), including Ovid's Medline, Embase, Emcare and PsycINFO; Scopus; Web of Science Core Collection, the Directory of Open Access Journals; Informit and; ProQuest Dissertations and Theses Global. Review Methods: Eligible articles included peer‐reviewed literature documenting journey mapping methodologies and studies conducted in healthcare services. Reviewers used Covidence to screen titles and abstracts of located sources, and to screen full‐text articles. A table was used to extract data and synthesize results. Results: Eighty‐one articles were included. An acceleration of patient journey mapping research was observed, with 76.5% ( n = 62) of articles published since 2015. Diverse mapping approaches were identified. Reporting of studies was inconsistent and largely non‐adherent with relevant, established reporting guidelines. Conclusion: Patient journey mapping is a relatively novel approach for understanding patient experiences and is increasingly being adopted. There is variation in process details reported. Considerations for improving reporting standards are provided. Impact: Patient journey mapping is a rapidly growing approach for better understanding how people enter, experience and exit health services. This type of methodology has significant potential to inform new, patient centred models of care and facilitate clinicians, patients and health professionals to better understand gaps and strategies in health services. The synthesised results of this review alert researchers to options available for journey mapping research and provide preliminary guidance for elevating reporting quality.